Arbuscular mycorrhizal fungi enhanced coix responses to phosphorous forms but not for faba bean in intercropping systems, under controlled environment. (3rd April 2021) - Bei, Shuikuan; Xu, Meng; Lyu, Xinkai; Chen, Caixia; Li, Ailian; Qiao, Xu
Abstract: Cereal/legume intercropping typically provides overyielding, particularly in low‐input agriculture. We examined the role of arbuscular mycorrhizal fungi (AMF) in responses to different P forms [Ca10 (OH)2 (PO4 )6 (Ca‐P), sodium phytate (Na‐P), and KH2 PO4 (K‐P)] in coix ( Coix lacryma‐jobi L.)/faba bean ( Vicia faba L.) intercropping systems. Shoot biomass of coix was significantly affected by P forms but not for faba bean. The Na‐P and K‐P treatments significantly enhanced shoot P concentration of coix with AMF inoculation conditions, however, Na‐P and K‐P treatments significantly enhanced the shoot P concentration of faba bean without AMF inoculation conditions. Monoculture faba bean had greater concentrations of malate and citrate and lower pH values than in intercropping, and than in monoculture coix. The growth of intercropped coix was promoted by the neighboring faba bean. We conclude that the difference utilized strategies in P forms of coix and faba bean, which improved intercropping productivity. Core Ideas: Arbuscular mycorrhizal fungi inoculation enhanced biomass and P uptake of coix and faba bean. The presence of faba bean facilitated the growth of neighboring coix. Difference utilized strategies in P forms of coix and faba bean improved intercropping productivity.